2020
DOI: 10.1002/jctb.6491
|View full text |Cite
|
Sign up to set email alerts
|

Mass transfer limitations in binderless ZSM‐5 zeolite granules during adsorption of flavour compounds from aqueous streams

Abstract: BACKGROUND: Recently, a new process concept has been proposed to selectively adsorb wort off-flavours, i.e. aldehydes, from alcohol-free beers with hydrophobic zeolites. RESULTS: In this work, we investigated the uptake of a mixture of wort flavour compounds (2-methylpropanal, 2-methylbutanal, 3-methylbutanal, furfural, and methional), from a model solution onto binderless hydrophobic ZSM-5 zeolite granules in order to quantify mass transfer parameters and identify bottlenecks. Subsequently, the homogenous sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Mass transfer limitations can affect the overall monomer generation rate and, in general, should be avoided for optimal system operation [33] . Specifically for lignocellulosic biomass and microporous zeolites, the system is prone to internal mass transfer limitations due to the interaction of large lignin macromolecules with microporous solids [34] . In order to ensure absence of internal and external mass transfer limitations during delignification, we have studied the effect of biomass particle size in the delignification rate of birch wood (see the Supporting Information, Section 16) and concluded that there are no diffusional limitations for particles below 150 μm and a solvent flow rate of at least 0.5 mL min −1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Mass transfer limitations can affect the overall monomer generation rate and, in general, should be avoided for optimal system operation [33] . Specifically for lignocellulosic biomass and microporous zeolites, the system is prone to internal mass transfer limitations due to the interaction of large lignin macromolecules with microporous solids [34] . In order to ensure absence of internal and external mass transfer limitations during delignification, we have studied the effect of biomass particle size in the delignification rate of birch wood (see the Supporting Information, Section 16) and concluded that there are no diffusional limitations for particles below 150 μm and a solvent flow rate of at least 0.5 mL min −1 .…”
Section: Resultsmentioning
confidence: 99%
“…The systematic rate‐limiting step analysis suggests that it is necessary to increase both solvolytic and catalytic reaction rates to enhance the phenolic monomer yield. Homogeneous acid addition is known to increase β‐O‐4 bond cleavage through hydrolysis, leading to a higher delignification rate [26,34] . Nevertheless, acid‐catalyzed lignin depolymerization may also lead to more severe lignin recondensation [18] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mass transfer limitations can affect the overall monomer generation rate and, in general, they should be avoided for optimal system operation [29] . Specifically for lignocellulosic biomass and microporous zeolites, the system is prone for internal mass transfer limitations due to the interaction of large lignin macromolecules with microporous solids [36] . In order to ensure absence of internal and external mass transfer limitations during delignification, we have studied the effect of biomass particle size in the delignification rate of birch wood (See ESI Section 16) and concluded that there are no diffusional limitations for particles below 150 m and a solvent flowrate of at least 0.5 mL/min.…”
Section: Rate Limiting Step Analysismentioning
confidence: 99%